Trend and Reasons of Women Towards the Choice for Place of Delivery: Evidence from Mics 2017-18 Punjab, Pakistan: Choice of Place of Delivery - Zeeshan, Muhammad; Isaac Shahzad; Shazia Hayat (Medical Journal of South Punjab, 2023)
Objective: To assess the attitudes and reasons of women towards the choice for place of delivery as per the data from the Multiple Indicators Cluster Survey (MICS) 2017-18, Punjab, Pakistan.Material and methods: Observational Study conducted at 36 districts of the Punjab, 2017-18A total of 53,840 households were drawn as the sample size from 2,692 sample clusters, out of which 1,893 were rural clusters and 799 were urban clusters. From 53,840 households, 52,765 households occupied and 51,660 were successfully interviewed. Therefore, the response rate was 97.9%. According to survey results, 79,510 women had been eligible for interview of age group 15-49 years. Out of which 74,010 women were interview successfully with the response rate 93.1%. Further, out of these 74,010 women, there were 26,980 women who had ever or currently married, and out of these women 15,656 women gave birth in the last two years. In our study, we considered the place of delivery as an outcome variable and wanted to identify the associated socio-demographic and socioeconomic characteristics that were expected to be responsible for shifting the trend from the public to the private sector for delivery. To check the association and for statistical testing of hypothesis, Chi-square test for association was applied. We also applied multinomial logistic regression to identify the predictors for the place of delivery by using SPSS. P-value ?0.05 was considered as significant.Results: Majority of the women (43.5%) delivered their babies in the private sector while (29.7%) of women delivered their babies in public sector hospitals, and (26.4%) women prefered home delivery. In the comparison of area of residence, urban women compared to rural women were more likely to choose public sector hospitals for their deliveries OR=1.02 (0.94-1.09) 95% CI, p=0.000, for home deliveries OR=1.293 (1.154-1.45) 95% CI, p=0.000 and for other OR=2.341 (1.196-4.582)95% CI, p=0.013. In the comparison of regions of Punjab, the women of South and Central Punjab were more likely to choose private sector hospitals for delivery, OR=1/0.535=1.87 (0.478-0.600)95% CI, p=0.000 and OR=1/0.624=1.61 (0.564-0.690)95% CI, p=0.000, respectively. The women who get antenatal care had 2.84 times more chances, as compared to the women who did not get antenatal care visits, to deliver in the private sector OR=0.353 (0.213-0.538)95% CI, p=0.000. About the model fitting, chi-square value=3527.06, Cox & Snell=0.202 and p=0.000 suggested that the predictors in the model had a significant effect.Conclusion: Overall women prefer to undergo childbirth process in private sector hospital while women of urban area prefer public sector hospital. It may be related to facilities present in private sector hospitals or it may due to the fact that public healthcare facilities are not accessible to everybody especially in rural areas. In modern era, still many women prefer home delivery.